2008
DOI: 10.1007/s11148-008-9033-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the structure and properties of hearth carbon blocks on premature shutdown of electrolytic baths

Abstract: Premature shutdown of electrolytic baths after a short service life leads to an increase in the cost of aluminum and serious economic losses. The most important element governing the service life of an electrolytic bath is the hearth that is lined with refractory hearth blocks. Presence of one concealed crack, that is exposed in the start-up period, may lead to failure of the whole electrolyzer in the first year of service. There are many producers and users of hearth blocks, and there are many specifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The material considered is a continuation of the cycle of articles for evaluating the characteristics of carbon hearth blocks for aluminum electrolyzers [1,2] it has been shown that the size of permeable pores is a critical property of the structure of blocks from the point of view their service life. This conclusion was drawn on the basis of simulating movement of electrolyte through permeable pores of hearth blocks and was confirmed by experimental observations.…”
mentioning
confidence: 99%
“…The material considered is a continuation of the cycle of articles for evaluating the characteristics of carbon hearth blocks for aluminum electrolyzers [1,2] it has been shown that the size of permeable pores is a critical property of the structure of blocks from the point of view their service life. This conclusion was drawn on the basis of simulating movement of electrolyte through permeable pores of hearth blocks and was confirmed by experimental observations.…”
mentioning
confidence: 99%